Whistler Wave Interactions With Superthermal Electrons on Martian Crustal Magnetic Fields: Bounce‐Averaged Diffusion Coefficients and Time Scales. Issue 6 (26th May 2021) - Shane, Alexander; Liemohn, Michael
Abstract: Pitch angle distributions of high‐energy superthermal electrons (> 100 eV) observed at Mars show evidence of a ubiquitous energization process occurring on dayside crustal magnetic fields. Wave–particle interactions have been put forth as one explanation and in this study we investigate if the conditions are right at Mars for this process to occur regularly. The resonant energy of electrons is dependent on not only the whistler wave frequency and normal angle but also the characteristic energy of the plasma environment. The characteristic energy is determined by the magnetic field strength and thermal electron density, both measured quantities by the Mars Atmosphere and Volatile EvolutioN mission. Bounce‐averaged diffusion coefficients are calculated using a typical characteristic energy profile and observed wave parameters. Time constants are also calculated and it is shown that wave–particle interactions are more efficient than Coulomb collisions. Low‐energy electrons have fast wave–particle interaction time scales and electrons can be scattered across the source cone and energized. High‐energy electrons have slow wave–particle interactions time scales and electrons energized to these energies will become trapped and modify the pitch angle distribution. Modeling the evolution of the electron distribution function will provide more insight into the process. Key Points: Low‐energy photoelectrons at Mars have fast wave–particle interaction time scales and can be scattered across the source cone High‐energy photoelectrons have slow wave–particle interaction time scales which restrict scattering across the source cone Trapped photoelectrons energized to high energies by whistler waves can then modify the high‐energy distribution